Clarifying changes in student empathy throughout medical school: a scoping review - Ferreira-Valente, M. Alexandra (2017)
Despite the increasing awareness of the relevance of empathy in patient care, some findings suggest that medical schools may be contributing to the deterioration of students' empathy. Therefore, it is important to clarify the magnitude and direction of changes in empathy during medical school. We employed a scoping review to elucidate trends in students' empathy changes/differences throughout medical school and examine potential bias associated with research design. The literature published in English, Spanish, Portuguese and French from 2009 to 2016 was searched. Two-hundred and nine potentially relevant citations were identified. Twenty articles met the inclusion criteria. Effect sizes of empathy scores variations were calculated to assess the practical significance of results. Our results demonstrate that scoped studies differed considerably in their design, measures used, sample sizes and results. Most studies (12 out of 20 studies) reported either positive or non-statistically significant changes/differences in empathy regardless of the measure used. The predominant trend in cross-sectional studies (ten out of 13 studies) was of significantly higher empathy scores in later years or of similar empathy scores across years, while most longitudinal studies presented either mixed-results or empathy declines. There was not a generalized international trend in changes in students' empathy throughout medical school. Although statistically significant changes/differences were detected in 13 out of 20 studies, the calculated effect sizes were small in all but two studies, suggesting little practical significance. At the present moment, the literature does not offer clear conclusions relative to changes in student empathy throughout medical school.